Impact of Smart City Planning and Construction on Community Governance under Dynamic Game - Jie Guo; Wenhao Ling (Complexity)
We present a research on smart city planning and community governance using dynamic game methods, analyze the current status and problems of the current smart community service system, and put forward countermeasures and suggestions based on the global smart community development experience. Through smart city planning and construction, the game model of government governance and information sharing between communities and decision making is obtained, and the two-dimensional replication dynamic system equations of smart city planning and construction agencies and communities are obtained from smart city planning and construction. The evolutionary stability strategy and a united front are analyzed. The strategy achieves the ideal stable conditions. We define the relevant definition of a smart community and discuss the purpose and significance of the research, especially the importance and necessity of the construction of the smart community. Based on the current situation of the construction of smart communities, we conduct specific research, discuss the deficiencies and shortcomings in the current construction of smart communities, and find out the causes of these problems. Finally, based on learning from the relevant work experience, corresponding improvement measures are proposed for the existing problems from the united front, top-level design, social participation, platform construction, and talent training.